Exploring Secondary Enrolment and GDP Growth in Nepal - Timsina, Tirtha Raj; Pokharel, Bandana (Journal of Research and Development, 2024)
Education is crucial for the advancement of every nation. The paper explores the importance of secondary education in human capital development and economic growth. It investigates the existing gender disparities in enrolment rates. This article aims to investigate the relationship between secondary level student enrollment rates and the Gross Domestic Product (GDP) in Nepal. It also explores the impact of educational gender disparity on economic development and provides insights into potential policy implications. Data from various sources, including the Ministry of Education of Nepal and the World Bank, are utilized to analyze trends in enrolment rates and GDP from 2011 to 2021. Data has qualitatively analyzed to investigate the link between secondary enrollment and GDP in Nepal. Pearson’s correlation and linear regression are utilized for thorough examination. The study has found no clear connection between secondary enrollment and GDP in Nepal. Surprisingly, as enrollment rates decrease, GDP seems to rise, suggesting that secondary school enrollment does not notably affect GDP in the country.